(untitled) (Research, Society and Development, 2021)
Introduction: This study aimed to identify the epidemiological profile of drowning victims in the State of Pará from 2010 to 2019. Objective: To trace the epidemiological profile of drowning deaths in the State of Pará from 2010 to 2019. Methods: Analysis of data obtained through the online platform of the Informatics Department of the Unified Health System (DataSus). Results: In the period, 3,144 deaths were registered due to accidental drowning and submersion, of which 82.6% were male and self-declared brown (82.54%). The age group with the highest number of cases was 20 to 29 years old, followed by the age group 1 to 4 years old. The municipalities that registered the highest number of deaths were Belém, Marabá and Santarém. Conclusion: There is a need for further discussions on the subject, as data on the characterization of the epidemiological profile of drowning victims will allow specific preventive actions for certain age groups in locations and populations where these numbers are more expressive.